Angular momentum transfer from photon polarization to an electron spin in a gate-defined quantum dot - Takafumi Fujita (Nature Portfolio, 2019)
Gate-defined quantum dots offer a way to engineer electrically controllable quantum systems with potential for information processing. Here, the authors transfer angular momentum from the polarization of a single photon to the spin of a single electron in a gate-defined double quantum dot.